MODELING OCCURRENCE AND GROWTH OF CANCERS IN THE COLLECTIVE INTERACTION OF LIVE TISSUE CELLS EXCHANGING CHEMICAL AND MECHANICAL SIGNALS - Bratsun, D.A.; Zakharov, A.P.; Krasnyakov, I.V.; Lyushnin, A.V.; Merkuriev, D.V. (Perm Federal Research Centre Journal, 2017)
In this paper, we propose a chemo-mechanical model of cancer tumor occurrence and development in a quasi-two-dimensional epithelial tissue. The model includes the individual dynamics of each cell which depends on the change of its shape and volume, location in tissue, intercalation and ability to divide. We have introduced two series of cells, normal and cancer ones, which differ in the set of chemical and mechanical parameters. In this paper it is assumed that cancer cells arise from a local failure of spatial synchronization of circadian rhythms. The circadian pattern formation is produced due to transcription/translation processes inside epithelial cells and the exchange of chemical signals between cells. In order to calibrate the complex system parameters we have used a large number of microphotographs representing the morphology of both normal and cancer cells. Both deterministic and stochastic descriptions of the system have been applied. Numerical study of evolutionary dynamics of the model has shown different protein patterns, some of which can provoke tumor occurrence. Variations in the system parameters have allowed reproducing different types of carcinomas including both invasive and non-invasive types. The model we developed can be used for a detailed study of the influence of targeting drugs on tumor cells.